The Impact of Infrastructure Spending in Sub-Saharan Africa : A CGE Modeling Approach - Perrault, Jean-François (2012)
The authors constructed a standard computable general equilibrium (CGE) model to explore the economic impact of increased spending on infrastructure in six African countries: Benin, Cameroon, Mali, Senegal, Tanzania, and Uganda. The basic elements of the model are drawn from EXTER, adjusted to accommodate infrastructure externalities. Seven sectors were considered: food crop agriculture, export agriculture, mining and oil, manufacturing, construction, private services, and public services. Four sets of simulations were conducted: baseline nonproductive investments, roads, electricity, and telecoms. For each set of simulations, five funding schemes were considered: reduced public expenditure; increased value-added taxes; increased import duties; funding from foreign aid; and increased income taxes. In general, the funding schemes had similar qualitative and quantitative effects on macro variables. For road and electricity investment, there were relatively large quantitative differences and some qualitative differences among funding schemes at the macro level. Sectoral analysis revealed further disparities among countries and investment types. The same type of investment with the same funding sources had varying effects depending on the economic structure of the sector in question. The authors find that few sectors are purely tradable or non-tradable, having instead variable degrees of openness to trade. If the current account needs to be balanced, funding investment through foreign aid produces the strongest sectoral effects because strong price and nominal exchange rate adjustments are needed to clear the current account balance. In addition, the capital/labor ratio of each sector plays an important role in determining its winners and losers.